2016
DOI: 10.1103/physrevlett.116.060601
|View full text |Cite
|
Sign up to set email alerts
|

Splitting of the Universality Class of Anomalous Transport in Crowded Media

Abstract: We investigate the emergence of subdiffusive transport by obstruction in continuum models for molecular crowding. While the underlying percolation transition for the accessible space displays universal behavior, the dynamic properties depend in a subtle nonuniversal way on the transport through narrow channels. At the same time, the different universality classes are robust with respect to introducing correlations in the obstacle matrix as we demonstrate for quenched hard-sphere liquids as underlying structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 74 publications
2
44
0
Order By: Relevance
“…Above a critical obstacle density, the test particle can no longer explore the whole environment but stays trapped and long-range transport is effectively suppressed. Höfling et al have observed that in two dimensions and close to the critical density diffusive and ballistic particles show the same subdiffusive motion in a random Lorentz gas [44,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Above a critical obstacle density, the test particle can no longer explore the whole environment but stays trapped and long-range transport is effectively suppressed. Höfling et al have observed that in two dimensions and close to the critical density diffusive and ballistic particles show the same subdiffusive motion in a random Lorentz gas [44,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The statistics of having a narrow channel can be modified by introducing structural correlations into the system. Relying on a quenched hard-sphere host structure the probability to find such narrow channels becomes larger than for the uncorrelated Lorentz gas [55]. This observation holds both for the infinite cluster only as well as averaged over all pores of the system.…”
Section: Splitting Of Universality Classesmentioning
confidence: 57%
“…Yet, apart from changing the value of this probability density the changes induced by the packing are smooth deformations with respect to the original Lorentz model. Simulation results for the mean-square displacement δr 2 ∞ (t) for ballistic tracers confined to the infinite cluster reveal that the walk dimension d w remains the same for all packing fractions [55]. Therefore the conclusion is that the statistics of the narrow channel is irrelevant as long as the probability density extrapolates to a constant for small channel widths.…”
Section: Splitting Of Universality Classesmentioning
confidence: 76%
See 2 more Smart Citations